Review on Soft Mobility Infrastructure Design Codes - Chang Chen; Zoi Christoforou; Nadir Farhi (Applied Sciences)
Soft mobility is gaining popularity in urban spaces due to its various benefits in terms of carbon footprint, air quality, congestion mitigation, and public health. Soft mobility infrastructure mainly includes urban road adjustments to accommodate pedestrian and bicycle flows. Relevant design codes are being developed worldwide, and important investments are being made in soft mobility. This paper provides a review and comparative analysis of 17 design codes and regulations from different countries and regions across the world. Furthermore, the German road design code for motorized traffic is used as a reference to assess the level of detail and eventual gaps in the soft mobility infrastructure design codes. Results indicate that, in contrast to road codes, soft mobility infrastructure codes vary significantly from country to country. Most importantly, the limit and recommended values of geometric parameters are fewer in number and less documented compared to road design parameters. Evidence-based recommendations are needed to enhance the design, construction, operation, maintenance, and safe management of soft mobility infrastructure.